THE CORRELATION BETWEEN STRESS LEVEL AND PREMENSTRUAL SYNDROME IN FINEL LEVEL NURSE STUDENTS - Wahyuni, W; Dewi, Diana Rosalina Kartika (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Stress is a phenomenon that occurs quite often in everyday life that we cannot avoid and will be experienced by each person. Stress is a condition that can be caused by several things such as uncontrolled physical demands, the environment, and social situations. Premenstrual syndrome (PMS) is a common problem that is often encountered by women which includes a collection of emotional and physical symptoms that occur in women in the 2-14 days before the onset of menstruation, or in the luteal phase of the menstrual cycle and then subsides soon after the onset of menstruation. College students are one of the groups that have a high potential for experiencing premenstrual syndrome due to increased levels of stress during academic education Objective: This study aims to determine the relationship between stress levels and premenstrual syndrome symptoms in final year nursing students. Methods: This type of research is observational with a cross-sectional study approach. The sampling technique used was purposive sampling, with the number of respondents as many as 115 final year D3 nursing students at Kusuma Husada University Surakarta in January. The instrument used to measure the level of stress is the Kessler Psychological Distress Scale (K10) and to measure the level of premenstrual syndrome using the Shortened Premenstrual Assessment Form (SPAF). Results: The results of the study using the Sperman rho' test, it was found that the p-value was 0.000 < 0.05, which means that there is a significant relationship between stress levels and premenstrual syndrome, and a correlation of r = 0.846 which means the relationship is strongly correlated with the direction of the correlation. positive Conclusion: The heavier the stress level, the more severe the premenstrual syndrome symptoms experienced.